2021
DOI: 10.1155/2021/6229460
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Mesenchymal Stem Cells with Ascorbic Acid and N-Acetylcysteine on TNF-α, IL 1β, and NF-κβ Expressions in Acute Pancreatitis in Albino Rats

Abstract: Severe acute pancreatitis (SAP) is a necrotic pancreatic inflammation associated with high mortality rate (up to 70%). Bone marrow (BM) mesenchymal stem cells (MSCs) have been investigated in pancreatic cellular regeneration, but still their effects are controversial. Therefore, the present study is aimed at examining the enrichment of the stem cells with ascorbic acid (AA) and N-acetylcysteine (NAC) and explore their combined action on the expression of the inflammatory cytokines: interleukin 1β (IL 1β), tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…TNF-α can also activate NF-κB, and further cause a magnified inflammatory reaction [ 22 ]. Therefore, regulation of TNF-α could not only alleviate the symptoms of AP, reduce the release of inflammatory mediators, but also inhibit NF-κB activation [ 23 ]. In this study, we found that TFC markedly inhibited the production of TNF-α in both in vivo (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…TNF-α can also activate NF-κB, and further cause a magnified inflammatory reaction [ 22 ]. Therefore, regulation of TNF-α could not only alleviate the symptoms of AP, reduce the release of inflammatory mediators, but also inhibit NF-κB activation [ 23 ]. In this study, we found that TFC markedly inhibited the production of TNF-α in both in vivo (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The cells were then trypsinized with 0.25% trypsin (Sigma, St. Louis, MO, USA, T1426) in 1 mL EDTA (Sigma, St. Louis, MO, USA, E6758) for five minutes at 37 °C and centrifuged at 2400 rpm for 20 min. The first passage was performed with the suspension and incubation of the cell pellets in 25 cm 2 culture flasks [ 31 , 44 ]. The adipose tissue was taken from the abdomen of Sprague Dawley albino rats after their sacrifice.…”
Section: Methodsmentioning
confidence: 99%
“…249900 (Rn_Tnfrsf1a_1_SG QuantiTect Primer Assay, ID QT00388346; Rn_Il1b_1_SG QuantiTect Primer Assay, ID QT00181657; and Rn_Nfkb2_1_SG, ID QT00396823), with the housekeeping gene ACTB Primer sequence. All the samples were analyzed using the 5-plex Rotor-Gene PCR Analyzer (Qiagen, Hilden, Germany) with the 2ΔΔCt method [ 44 , 49 ].…”
Section: Methodsmentioning
confidence: 99%
“…The implication is that inflammatory cell damage from AP is not limited to the exocrine compartment but also the endocrine compartment, and specifically the islet cells, which can exacerbate AP severity. 11 In mice with preexisting DM mimicked via either permanent (Ins2Akita) or conditional (EL-CreER/−/IRfl/fl or PACIRKO) loss of insulin signaling, the severity of AP in 2 models of AP induction (palmitoleic acid/ethanol and cerulein) was far worse than in control mice, 12 providing a link between immune changes in the context of DM and inflammation induced by AP. Beyond these studies, there is little evidence of immune-mediated cytotoxicity linking AP and DM, although other AP-associated molecular signals may contribute to DM development.…”
Section: Animal Models: Understanding the Role Of The Immune System I...mentioning
confidence: 99%
“…In a rat model of cerulein-induced AP, islet cell integrity was maintained by the addition of bone marrow–derived mesenchymal stem cells in the presence of ascorbic acid and N -acetylcysteine, which effectively blocked IL-1ß, TNF-α, and nuclear factor κB. The implication is that inflammatory cell damage from AP is not limited to the exocrine compartment but also the endocrine compartment, and specifically the islet cells, which can exacerbate AP severity 11 . In mice with preexisting DM mimicked via either permanent (Ins2Akita) or conditional (EL-CreER/−/IRfl/fl or PACIRKO) loss of insulin signaling, the severity of AP in 2 models of AP induction (palmitoleic acid/ethanol and cerulein) was far worse than in control mice, 12 providing a link between immune changes in the context of DM and inflammation induced by AP.…”
Section: Animal Models: Understanding the Role Of The Immune System I...mentioning
confidence: 99%